(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The securities market is a critical component of the financial system, providing opportunities for banks to enhance their profitability, diversify their portfolios, and contribute to economic growth. This article examines various strategies to improve a bank’s activity in the securities market, focusing on risk management, technological advancements, regulatory compliance, and customer relationship management. By adopting these strategies, banks can better navigate the complexities of the securities market, optimize their operations, and achieve sustainable growth.